Prerequisite knowledge and time of testing in learning with animations and static pictures: Evidence for the expertise reversal effect. (June 2021) - Kühl, Tim
Abstract: An animation can have an informational advantage over a static picture by depicting dynamic features. The aim of this study was to investigate whether the provision of prerequisite knowledge can help learners infer dynamic features from a static picture. It was assumed that this supposedly more active processing with a static picture would result in longer lasting knowledge representations. A 2 × 2 × 2 between-subjects design with visualization format (static picture vs. animation), prerequisite knowledge (provided vs. not provided), and time of testing (immediate vs. one week later) was used ( N = 260). The results of a transfer test showed that learners with low prerequisite knowledge benefited from the animation, but this was not the case for learners with high prerequisite knowledge. Time of testing had no influence. In line with the expertise reversal effect, prerequisite knowledge not only fostered learning with the static picture but also hindered learning with the animation. Highlights: Learning with an animation fostered the acquisition of dynamic factual knowledge. An expertise reversal effect emerged for transfer and non-dynamic factual knowledge. Prerequisite knowledge tended to be beneficial for learners with static pictures. Prerequisite knowledge was detrimental for learners with an animation. Time of testing had no moderating influence.